Круг: рассказы / Татьяна Толстая - Толстая Татьяна Никитична (Подкова, 2003)
Экземпляры: ФИЛ (20180924) / Инвентарный номер: 1104182 / Цена: / Сис.шифр: Р2 / Авт.знак: Т 52 / ГРНТИ: 17.82.32 / ББК: 84(2)